EKSISTENSI PEREMPUAN DAN POKOK-POKOK PIKIRAN FEMINISME DALAM NOVEL KUBAH DI ATAS PASIR KARYA ZHAENAL FANANI - Priyadi Priyadi (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
This study background of the desire of researchers to discover existence and the struggle of female characters to survive in the rigors of the world. The role of women is influential in life and education in literary works which are socio-cultural products.This research aim to describe and explainabout: (1) the existence of womencharachters,(2) the main ideas of feminism contained in the Kubah di Atas Pasir novel by Zhaenal Fanani. This research used qwalitative descriptive by feminism approach. The data that has been analyzed by interactive model of analysis techniques with three steps of activity: (1) data reduction, (2) presenting data, (3) conclusion and verrification.The results of research were as follows: (1) The existence of women contained in the Kubah di Atas Pasir novel included: the freedom to vote for women, injustice of gender for women, the buffetings of women in education, and the buffetings of women in surroundings. (2) The main ideas of feminism that are: women character’s independency, liberal feminism analysis in the novel.